Processo de afirmação da obrigatoriedade do ensino da música na escola: aspectos sociais, educacionais e legais. - Mariano, Daniel Augusto de Lima (2012)
This dissertation presents discussions about Musical Education in the context of Public Policies in the Education field. The research aims at the institutionalization process of mandatory Music teaching in public schools in the city of João Pessoa, based on the Law 11.769/2008. To accomplish all this, it was necessary to understand the present forces in the trajectory of educational policies that enabled the emergence of Law 11.769/2008 establishing the mandatory Music teaching in elementary Brazilian school. Historical periods were analyzed with the emergence of Music education since the colonial period, after its transformation in educational reforms in the Empire and posteriorly its nationalization during the Vargas Age (1930- 1945) with the Orpheonic Singing project, directed by maestro Heitor Villa-Lobos. After the decline of such a project and the exclusion of Music as a subject in school curricula from the LDB of 1961 and 1971, arises a movement of musicians, music educators and politicians who aimed at the return of Music as a mandatory content at elementary school. From the Foucaultian concept of Discourse Analysis, we sought to understand the context of the Law creation 11.769/2008 and the prospects of its implementation in public basic school, in general, and specifically in the city of João Pessoa.